Kritik ekologi cerpen “O” Karya Benny Arnas dalam Kompas 17 April 2022: Perspektif Greg Garrard - Nuni Anggraeni (Universitas Lampung, 2023)
The development of the oceans is now starting to be threatened due to climate change and ecosystem imbalances that occur in nature. It is important for us as the nation's successors to preserve and cultivate the surrounding environmental ecosystem for a better environment. This study aims to examine the wisdom of the sea through the behavior and thoughts of the characters in the short story “O” by Benny Arnas using a descriptive qualitative method. The research data source comes from kompas.id with a short story entitled